Electrochemical synthesis of 1, 2, 4-triazole-fused heterocycles. Issue 8 (14th March 2018) - Ye, Zenghui; Ding, Mingruo; Wu, Yanqi; Li, Yong; Hua, Wenkai; Zhang, Fengzhi
Abstract : A reagent-free electrochemical synthesis of valuable 1, 2, 4-triazolo[4, 3- a ]pyridines and related heterocycles was developed. Abstract : A reagent-free intramolecular dehydrogenative C–N cross-coupling reaction has been developed under mild electrolytic conditions. In this atom- and step-economical one-pot process, valuable 1, 2, 4-triazolo[4, 3- a ]pyridines and related heterocyclic compounds could be synthesized efficiently from commercially available aliphatic or (hetero)aromatic aldehydes and 2-hydrazinopyridines. Various functional groups are compatible with this metal- and oxidant-free protocol which can be carried out on a gram scale easily. This novel method was applied to the synthesis of one of the top-selling drugs Xanax and late stage functionalization for generating chemical diversity in biologically relevant lead molecules.